TINGKAT PENGETAHUAN SISWA SMU TENTANG NARKOBA DI WILAYAH BATURADEN DAN PURWOKERTO TIMUR - Sumarwati, Made; Purnawan, Iwan; Mursiyam, Mursiyam (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2009)
The drugs abuse is teenagers are complex problem. It is not only about teenagers, but also about another aspects like family, enviroment, school, friend. Health?s provider and laws government officer. Sub-province of Banyumas is region which have most drugs abuse?s case that can be exposed. According to Kasat Narkoba Banyumas, at 2006, they can catch 36 drugs abuser. Ten among others are students of senior high school. One of the action for drugs abuser?s handling is preemptive way. This way is done by socialization of drugs to increase the knowledge of teenanger about drug abuse. The aim of research is to know knowledge?s level of Senior High School?s student about drug abuse at the districts of Baturraden by cluster sampling. The students as respondents who involve in this research are from class three till class seven. The amount of respondents in this research is 395. The processing data?s method that use is data?s tabulation pursuant to cumulative frequency. The research?s result conclude that knowledge?s level of Senior High School?s student about drug abuse in region of Purwokerto Timur is Baturraden included in good category. It?s show by score more than 26, namely 27,67.